Age at First Delivery and Osteoporosis Risk in Korean Postmenopausal Women: The 2008-2011 Korea National Health and Nutrition Examination Survey (KNHANES). - Bo Hyon Yun; Yun Rak Choi; Young Sik Choi; SiHyun Cho; Byung Seok Lee; Seok Kyo Seo (PLoS ONE, 2015)
It has been reported in several studies that there may be a significant correlation between reproductive history and the risk of osteoporosis due to the effect of estrogen. Under this hypothesis, however, it is unclear whether the age at first delivery has any major influences on the risk of osteoporosis. Therefore, this study aimed to investigate the relationship between the age at first delivery and the risk of osteoporosis in Korean menopausal women. This study was performed using data from the 2008-2011 Korea National Health and Nutrition Examination Survey and included 2,530 Korean postmenopausal women. The diagnosis of osteoporosis was made using the World Health Organization T-score criteria (T-score ≤ -2.5, at the femoral neck or lumbar spine). Participants were categorized into 3 groups according to age at first delivery: ≤ 23, 24-29, and ≥ 30 years. Older age, lower body mass index, lower calcium intake, later menarche, and earlier menopause increased the risk of osteoporosis, whereas hormone therapy and oral contraceptive use were associated with a decreased risk of osteoporosis. Postmenopausal women whose first delivery occurred at age 24-29 years were shown to have a significantly increased risk of osteoporosis (odds ratio, 2.124; 95% confidence interval, 1.096-4.113; P = 0.026) compared to those who first gave birth after the age of 30 years. These findings suggest that postmenopausal women whose first delivery occurred in their mid to late 20s, a period during which bone mass slowly accumulates to the peak, are at an increased risk of osteoporosis.